THE FACTORS WHICH INFLUENCE EARNINGS MANAGEMENT WITH GOOD CORPORATE GOVERNANCE AS MODERATING VARIABLE IN MANUFACTURE COMPANIES LISTED IN BEI - Triboy, Besli Saragih (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to find out some factors which influenced earnings management consisted of Information asymmetry, firm size, leverage, institutional ownership, and profitability with good corporate governance proxied   with independent board of commissioners and audit committee as moderating variable in manufacture companies listed in BEI in the period of 2013-2015. The research used hypothetical test or explanatory research method. The population was 144 manufacture companies listed in BEI, and 106 of them were used as the samples, taken by using proportional random sampling technique. The result of the research showed that, simultaneously, Information asymmetry, firm size, leverage, institutional ownership, and profitability influenced earnings management. Partially, Information asymmetry and profitability influenced earnings management, while firm size, leverage, and institutional ownership did not have any influence on earnings management. Good corporate governance which proxied with independent board of commissioners and audit committee was moderating variable in this research in which independent board of commissioners and audit committee were not the variables which could moderate the influence of Information asymmetry, firm size, leverage, institutional ownership, and profitability on earnings management.